2010
DOI: 10.1038/nature09574
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of polycomb-repressed genes by ZRF1

Abstract: Covalent modification of histones is fundamental in orchestrating chromatin dynamics and transcription. One example of such an epigenetic mark is the mono-ubiquitination of histones, which mainly occurs at histone H2A and H2B. Ubiquitination of histone H2A has been implicated in polycomb-mediated transcriptional silencing. However, the precise role of the ubiquitin mark during silencing is still elusive. Here we show in human cell lines that ZRF1 (zuotin-related factor 1) is specifically recruited to histone H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 31 publications
7
139
1
Order By: Relevance
“…In shZrf1 cells we noted stabilization of Ring1b at chromatin in agreement with our previous findings. 18 Med12 levels at chromatin remained unaltered but recruitment of Cdk8 was drastically impaired in Zrf1 knockdown cells. Importantly, knockdown of Zrf1 has no impact on the mRNA and the protein levels of Cdk8 (Figs.…”
Section: Zrf1 Assembles the Cdk8 Module During Differentiationmentioning
confidence: 95%
See 2 more Smart Citations
“…In shZrf1 cells we noted stabilization of Ring1b at chromatin in agreement with our previous findings. 18 Med12 levels at chromatin remained unaltered but recruitment of Cdk8 was drastically impaired in Zrf1 knockdown cells. Importantly, knockdown of Zrf1 has no impact on the mRNA and the protein levels of Cdk8 (Figs.…”
Section: Zrf1 Assembles the Cdk8 Module During Differentiationmentioning
confidence: 95%
“…5F) is reminiscent of the function of Zrf1, which displaces PRC1 from chromatin to derepress Polycomb target genes. 18 To verify whether Zrf1 activates developmental target genes repressed by Med12 and Ring1b, we analyzed Zrf1 knockdown cells after stimulation with RA. We found that transcriptional activation of selected Med12-Ring1b target genes was dramatically impaired in shZrf1 cells (Fig.…”
Section: Zrf1 Associates With Activating Ncrnas During Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Richly et al (40) identified ZRF1 as an H2Aub-binding protein involved in differentiation-dependent transcriptional activation of Polycomb target genes. If reduced PRC2 activity on Polycomb group-repressed genes is an important early step in pushing the chromatin state toward one more permissive to transcription, then our in vitro cross-talk data may provide another layer of mechanistic explanation for H2Aub involvement in transcriptional derepression.…”
Section: Discussionmentioning
confidence: 99%
“…1 Our results suggest that ZRF1 exerts its function in a two-step mechanism, by initially displacing the Polycomb-repressive complex 1 (PRC1) from chromatin and subsequently acting together with histone H2A-specific deubiquitinases to facilitate transcriptional activation of its target genes. These findings demonstrate an ambiguity of the epigenetic monoubiquitin mark at histone H2A.…”
mentioning
confidence: 85%